Activation of PPARγ reduces N-acetyl-cysteine -induced hypercorticoidism by down-regulating MC2R expression into adrenal glands - Ventura, Raíssa D. (2020)
We previously demonstrated that oral supplementation with antioxidants induced hyperactivity of hypothalamus-pituitary-adrenal (HPA) axis, attested by hypercorticoidism, through an up-regulation of adrenocorticotrophic hormone (ACTH) receptors (MC2R) in adrenal. This study analyzed the role of peroxisome proliferator-activated receptor (PPAR)-γ on HPA axis hyperactivity induced by N-acetyl-cysteine (NAC). Male Swiss-Webster mice were orally treated with NAC for 1, 3, 5, 10, 15, or 18 consecutive days. The PPAR-γ agonist rosiglitazone and/or antagonist GW9662 were daily-injected i.p. for 5 consecutive days, starting concomitantly with NAC treatment. Rosiglitazone treatment inhibited NAC-induced adrenal hypertrophy and hypercorticoidism. Rosiglitazone also significantly reversed the NAC-induced increase in the MC2R expression in adrenal, but not steroidogenic acute regulatory protein (StAR). NAC treatment reduces the expression of PPARγ in the adrenals, but rosiglitazone did not restore the expression of this cytoprotective gene. In addition, GW9662 blocked the ability of rosiglitazone to decrease plasma corticosterone levels in NAC-treated mice. In conclusion, our findings showed that antioxidant supplementation induced a state of hypercorticoidism through down-regulation of PPARγ expression in the adrenals, in a mechanism probably related to a down-regulation of ACTH receptor expression.